Proteomic analysis of active multiple sclerosis lesions reveals therapeutic targets - Han, May H.; Hwang, Sun-Il; Roy, Dolly B.; Lundgren, Deborah H.; Price, Jordan V.; Ousman, Shalina S.; Fernald, Guy Haskin; Gerlitz, Bruce; Robinson, William H.; Baranzini, Sergio E.; Grinnell, Brian W.; Raine, Cedric S.; et al. (Nature, 2008)
Understanding the neuropathology of multiple sclerosis (MS) is essential for improved therapies. Therefore, identification of targets specific to pathological types of MS may have therapeutic benefits. Here we identify, by laser-capture microdissection and proteomics, proteins unique to three major types of MS lesions: acute plaque, chronic active plaque and chronic plaque. Comparative proteomic profiles identified tissue factor and protein C inhibitor within chronic active plaque samples, suggesting dysregulation of molecules associated with coagulation. In vivo administration of hirudin or recombinant activated protein C reduced disease severity in experimental autoimmune encephalomyelitis and suppressed Th1 and Th17 cytokines in astrocytes and immune cells. Administration of mutant forms of recombinant activated protein C showed that both its anticoagulant and its signalling functions were essential for optimal amelioration of experimental autoimmune encephalomyelitis. A proteomic approach illuminated potential therapeutic targets selective for specific pathological stages of MS and implicated participation of the coagulation cascade. Multiple sclerosis targets A large-scale proteomic analysis of tissue samples from multiple sclerosis (MS) lesions from different stages of the disease has identified proteins peculiar to brain lesions associated with different disease stages. Several new potential therapeutic targets were found. Two proteins in particular showed signs of damage during the chronic active period of the disease. One, called tissue factor, is involved in the initiation of blood clotting and the other, protein C inhibitor, in anti-inflammatory pathways. Administration of activated protein C or the anticoagulant hirudin slowed disease progression in a mouse model of multiple sclerosis, suggesting that the coagulation cascade has a previously unsuspected role in MS pathogenesis.